Prognostic factors for survival in patients with mucosal and ocular melanoma treated with ipilimumab: Turkish Oncology Group study. (March 2020) - Arzu Yaşar, H; Turna, Hande; Esin, Ece; Murat Sedef, A; Alkan, Ali; Oksuzoglu, Berna; Ozdemir, Nuriye; Sendur, MA Nahit; Sezer, Ahmet; Kılıckap, Saadettin; Utkan, Gungor; Akbulut, Hakan; et al.
Objective: To evaluate prognostic factors associated with the use of ipilimumab in patients with mucosal and uveal melanoma. Methods: In this multicenter, retrospective study, 31 patients with uveal and mucosal melanoma diagnosed between 2010 and 2017 were enrolled. Patients' characteristics, metastatic disease sites, treatment before ipilimumab therapy, performance status, hemoglobin, lactate dehydrogenase levels, B-RAF and c-kit mutation status, toxicity, and survival data were assessed for patients with mucosal and uveal melanoma. SPSS version 17 was used for statistical analysis. Kaplan–Meier method was used for survival analysis. The log-rank test was used for univariate analyses. The Cox regression analysis was used to test the association between multivariate variables and survival. The p-value of less than 0.05 was considered statistically significant. Results: Twenty patients had uveal and eleven patients had mucosal melanoma. The median overall survival was seven months (95% confidence interval: 1.1–12.7). In univariate analysis, while bone metastasis, anemia, high lactate dehydrogenase level, and more metastatic sites were associated with lower overall survival, better treatment response and administration of ipilimumab in first or second lines were associated with favorable overall survival. In multivariate analysis, only treatment response status and administration of ipilimumab in first or second lines were found to be significant as independent prognostic factors for survival. Conclusion: Ipilimumab therapy may be associated with increased survival, but this retrospective small N study makes that hard to definitely conclude.